Spiritual Mindfulness Based on Breathing Exercise terhadap Kecemasan dan Kadar Glukosa Darah pada Pasien DM Tipe 2 - Dina Trisnawati; Yayat Suryati; Susilawati Susilawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to compare the effectiveness of pharmacological therapy with pharmacological therapy accompanied by spiritual mindfulness based on breathing exercises on anxiety levels and blood glucose levels in type 2 DM patients. This study is a quasi-experimental study using a pretest-posttest design with a control group design. The results showed that there were differences in the level of anxiety of patients in the control group and the experimental group with a P-Value of 0.035 <0.05, and there were differences in the blood sugar levels of patients in the control group and the experimental group with a P-Value of 0.002 <0.05. In conclusion, pharmacological therapy interventions accompanied by spiritual mindfulness based on breathing exercises were proven effective in reducing anxiety and blood sugar levels in type 2 DM patients. Keywords: Type 2 DM, Blood Glucose, Anxiety, Mindfulness